Environmental life cycle assessment study of an external wall. (19th September 2022) - Ciarapica, Filippo Emanuele; Postacchini, Leonardo; Antomarioni, Sara; Loreto, Samantha Di; Perna, Costanzo Di
In the current economic scenario, sustainable development goals are pursued with the aim of creating a sustainable industrial scenario. Industrial sectors responsible for high levels of emissions and consumption, such as the construction industry, need to be thoroughly analysed, focusing on the use of recyclable and eco-sustainable materials. In this regard, this work proposes an environmental life cycle assessment study, which aims to quantify the environmental impacts of a standard designed external wall and evaluate the use of recycled materials in its insulation layer. An external wall with expanded polystyrene insulation has been chosen. Six environmental impact categories have been considered: 'acidification'; 'eutrophication'; 'global warming potential'; 'abiotic depletion – elements'; 'abiotic depletion – fossil fuels'; 'ozone layer depletion'. Results show that the reinforced concrete layer has the most significant contribution to all the analysed impact categories. Moreover, comparing the insulation layer with different percentages of recycled expanded polystyrene, it has been found that the impact categories majorly influenced are the 'global warming potential' and the 'abiotic depletion – fossil fuel'.